5E-Based Flipped classroom Teaching Model Templates for STEM Education - Noly Shofiyah; Fitria Eka Wulandari; Metatia Intan Mauliana; Lailatul Maghfiroh (Indonesian Journal of Cultural and Community Development, 2023)
This study focuses on the development of 5E-Based Flipped classroom Teaching Model Templates for STEM education. The aim is to assess the validity and reliability of the model across its content and construct validity. The findings suggest that the 5E-Based Flipped classroom Model for STEM Learning exhibits strong validity and reliability. The model is well-developed, supported by theory, effectively planned and implemented, and reliable in measuring the desired outcomes in STEM education. These results provide valuable insights for educators and researchers interested in adopting the 5E-Based Flipped classroom Model for STEM Learning in their educational settings. By utilizing these templates, educators can enhance their teaching practices and facilitate engaging and effective learning experiences for students in STEM subjects. Researchers can also benefit from these findings to further investigate the impact and effectiveness of the model in different educational contexts. Overall, the 5E-Based Flipped classroom Teaching Model Templates for STEM education offer a promising approach to foster student engagement, understanding, and achievement in STEM disciplines. Highlights: Validity and reliability assessment: The study evaluates the validity and reliability of the 5E-Based Flipped classroom Teaching Model Templates for STEM education, providing evidence of its strong validity and reliability. Effective teaching and learning: The model is well-developed, supported by theory, and effectively planned and implemented, enhancing teaching practices and facilitating engaging and effective learning experiences for students in STEM subjects. Potential for broader adoption and research: The findings offer valuable insights for educators and researchers interested in adopting the model, encouraging further investigation of its impact and effectiveness in different educational settings and contexts. Keywords: 5E-Based Flipped classroom Teaching Model Templates, STEM education, validity, reliability, engagement.